The effect of seed polymer coating technology to improve ecological restoration outcomes in Lowland Sand Fynbos - Mbombo, Bongiwe (Stellenbosch : Stellenbosch University, 2025)
Thesis (MScConEcol)--Stellenbosch University, 2025.